Assessment of indoor air quality in public preschool and its impact on respiratory function in Jeddah City, Saudi Arabia - Alsharif, Bayan Hashim; Alqutub, Sulafa Tarek; Khafagy , Abdullah; Alshareef , Maram (International Journal of Health Sciences, 2024)
Objectives: This research aimed to examine the connection between indoor air quality and respiratory function in preschool children, a topic that, to the best of our knowledge, has not been explored before. Methods: This cross-sectional study was conducted within the geographical location of the Ministry of Education of Jeddah. Four hundred preschool-aged children (4–6 years old) from four preschools were enrolled. Structured questionnaires and peak flow meter (PFM) were used to assess the overall health and pulmonary function of the participants. An air detector for formaldehyde (HCHO), volatile organic compound, and fine particulate dust matter and a carbon dioxide (CO2) detector with temperature and humidity monitors were used to measure the air pollutants. Results: A significant difference was observed in PFM measurement between the four preschools (P = 0.017). The highest PFM green zone value was identified in the North preschool (n = 32, 54.2%), and the lowest value was identified in the Central preschool (n = 21, 33.3%). Regarding the red zone, the highest value was observed in the Central preschool (n = 14, 22.2%) and the lowest in the North preschool (n = 1, 1.7%). PFM measurement in the green zone showed lower CO2 levels (P = 0.014) and temperature (P = 0.04) than those in the yellow and red zones. Conclusion: Children schooling in adequate ventilation environments had better respiratory function than those in inadequate environmental ventilation.